Desenvolvimento de infográfico animado sobre transtorno do espectro autista - Maia, Elisa Maria Bezerra (2020)
Autistic Spectrum Disorder (ASD), called autism, is currently considered a neurodevelopmental disorder, and difficulties in dealing with this situation are common after diagnosis. This work aimed to develop a series of three animated infographics on aspects and approaches to TEA in order to disseminate safe content to all interested audiences, especially the family of autistic individuals and health professionals. The methodological development took place in three phases: Design, Execution and Finishing, which are subdivided into eleven stages: agenda, requirements elicitation, data verification, analysis of similars, content development, information architecture, artwork, finishing, review , publication and critical analysis. The elicitation of requirements that took place between July and September 2019, counted on the participation of eleven specialists in TEA to assist in the construction and content approach, providing direction for the elaboration of compiled information that served as a basis for the construction of conceptual maps and prototypes, that were made available for the professionals' final considerations. After prototyping, we continued with the final design of the infographics and production of the animations, which took place between October 2019 and January 2020. At the end, associating texts, images, audios, animations and transitions, we compose three animated infographics: conceptual bases of Autism (aimed at the lay public in general), methods for stimulation and care for autistic individuals (tips for care in the family and community where the autistic lives) and health professional approaches and tools for interacting with autistic people (aimed at professionals in different areas who will deal with autistic individuals, but still have no knowledge on the topic). All videos are available on Youtube and on free access platforms, serving as an educational material that is easy to understand, encouraging the search for information and learning about the topic, to the interested public.